Determination of Student Opinions on Usage of Social Media and Mobile Tools in Student-Teacher, Student-Student Communication - Hasan Denizalp (International Journal of Emerging Technologies in Learning (iJET), 2019)
Since Depending on technological advances, development of social media and mobile applications today reshape communication, education and teaching system. The extent to which social media and mobile applications which are especially used by new generation youth frequently will be beneficial in student-teacher and student-student communication is becoming more and more important. This research is based on the opinions of students on the usage of social media and mobile applications in education which take considerable time of teachers and students, social networks and mobile applications were used with the purpose of communication in science and communication technologies for 12 weeks. Thirty-five teacher candidates attended the study. At the end of the application interviews were held with 20 students and according to the findings obtained, an effort was paid to determine the impact of social media and mobile applications in student-teacher and student-student communication. Discussions and recommendations on obtained findings were presented.